2000
DOI: 10.1046/j.1464-410x.2000.00247.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of seven human renal cell carcinoma cell lines

Abstract: and their tumour tissues, mutations in the VHL gene were found. The SNU-267 line had a frameshift mutation in the p53 gene. A missense mutation of the TGF-bRII gene was detected in the SNU-1272 line and the corresponding tissue. Analysis of the repeat sequences showed one cell line (SNU-349) to have MSI and the other six to have microsatellite stability. As MSI is a hallmark of the inactivation of mismatch repair genes, the presence of hMSH2 and hMLH1 mutations was investigated in all seven cell lines. An inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Here, we reported that the establishment of 10 RCC cell lines derived from human patient tumors. Only 10 of 125 patient tumors were able to be used in this regard (8.0% success rate), which is lower than that of other reports (18,19). Because of this reason, we used the nude mice to establish the RCC cell lines, and then used the SCID/beige mice to assess tumor burden and immune cell reconstitution.…”
Section: Discussionmentioning
confidence: 96%
“…Here, we reported that the establishment of 10 RCC cell lines derived from human patient tumors. Only 10 of 125 patient tumors were able to be used in this regard (8.0% success rate), which is lower than that of other reports (18,19). Because of this reason, we used the nude mice to establish the RCC cell lines, and then used the SCID/beige mice to assess tumor burden and immune cell reconstitution.…”
Section: Discussionmentioning
confidence: 96%
“…A previous analysis of seven renal carcinoma cell lines also identified a genetic alteration in hMLH1. 39 Perhaps the location of hMLH1 on the short arm of chromosome 3 has biologic relevance since this region is often genetically altered in clear cell RCC. 34 Haploinsufficiency at the hMLH1 locus may be an expected and frequent event in clear cell RCC predisposing some tumor cells to MMR deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, five cell lines were derived from clear cell RCC (SNU-228, -267, -328, -349, and -1272), one from granular RCC (SNU-482), and one from mixed clear and granular RCC (SNU-333). The mutational status of cell lines was confirmed for von Hippel-Lindau (VHL), p53, TGF-beta type II receptor (TGF-betaRII), hMSH2, and hMLH1 genes [92]. More recently, Chinese-origin cell lines named NRCC from the primary ccRCC and MRCC from the metastatic ccRCC were established from the primary tumor of a 49-year-old male ccRCC patient and the metastatic tumor of a 62-year-old male with ccRCC.…”
Section: Introductionmentioning
confidence: 99%